2020
DOI: 10.1016/j.ajpc.2020.100094
|View full text |Cite
|
Sign up to set email alerts
|

The role of traditional risk factors in explaining the social disparities in cardiovascular death: The national health and Nutrition Examination Survey III (NHANES III)

Abstract: Objective ─ To assess the role of traditional risk factors in explaining the association between cumulative social risk exposure and disparities in CVD death among US adults. Methods ─ The study included 15,906 participants from the Third National Health and Nutrition Examination Survey III who were CVD-free at enrollment. Baseline social risk factors (minority race, poverty-income ratio<1, education<12 grade, and living single) were used to create a cumulative social r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(14 citation statements)
references
References 24 publications
0
14
0
Order By: Relevance
“…Income disparity has been studied as a component of SES among NHANES participants in two recent studies. Zhang and colleagues studied NHANES III participants recruited in 1988–1994 and created a cumulative social risk score comprising of PIR < 1, minority race, education < 12th grade, and living single 12 . They observed that a higher cumulative social risk score was independently associated with 19% to 52% higher risk of CVD death 12 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Income disparity has been studied as a component of SES among NHANES participants in two recent studies. Zhang and colleagues studied NHANES III participants recruited in 1988–1994 and created a cumulative social risk score comprising of PIR < 1, minority race, education < 12th grade, and living single 12 . They observed that a higher cumulative social risk score was independently associated with 19% to 52% higher risk of CVD death 12 .…”
Section: Discussionmentioning
confidence: 99%
“…Zhang and colleagues studied NHANES III participants recruited in 1988–1994 and created a cumulative social risk score comprising of PIR < 1, minority race, education < 12th grade, and living single 12 . They observed that a higher cumulative social risk score was independently associated with 19% to 52% higher risk of CVD death 12 . Zhang et al subsequently studied NHANES participants recruited in 1988–1994 (NHANES III) and 1999–2014 (continuous cycles) 13 .…”
Section: Discussionmentioning
confidence: 99%
“…37,38 In summary, despite the many contrasting features between T2DM and SLE, both these clinical entities share a similar increased risk for developing CVD. [2][3][4][5] A search for a common denominator has left us with the prospect of NLRP3 inflammasomes as a potential suitable and quite appealing candidate that might explain the particularly aggressive nature of vascular disease and atherosclerosis progression found in T2DM and SLE patients.…”
mentioning
confidence: 99%
“…A series of well described risk factors have been traditionally linked to the development of ASCVD 2 . One of these risk factors is diabetes mellitus.…”
mentioning
confidence: 99%
See 1 more Smart Citation